2021
DOI: 10.1186/s13256-021-03021-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of CytoSorb therapy to treat critically ill coronavirus disease 2019 patients: a case series

Abstract: Background Acute respiratory distress syndrome is an important clinical presentation of respiratory complications caused by severe acute respiratory syndrome coronavirus 2, a novel coronavirus responsible for the ongoing pandemic. The disease is poorly understood, and immunopathogenesis is constantly evolving. Cytokine release syndrome remains central to pathology of coronavirus disease 2019. Antivirals, anticytokine treatment, and other pharmacological approaches have failed to treat it. CytoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another case series published by Mehtha et al, reported the use of Cytosorb after 72 hrs of ICU admission for 24 hrs reported a significant decrease in the levels of CRP and 100% survival rate 18 al, reported a case study of a 51 years old male COVID 19 patients who survived cytokine storm upon treating with Cytosorb and definite treatment 20 . Another case study conducted by Berlot et al, reported use of Cytosorb along with Tocilizumab reported a positive result in terms of extubation after 10 days of the therapy and radiological imaging suggestive of improvement in the lung fields 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case series published by Mehtha et al, reported the use of Cytosorb after 72 hrs of ICU admission for 24 hrs reported a significant decrease in the levels of CRP and 100% survival rate 18 al, reported a case study of a 51 years old male COVID 19 patients who survived cytokine storm upon treating with Cytosorb and definite treatment 20 . Another case study conducted by Berlot et al, reported use of Cytosorb along with Tocilizumab reported a positive result in terms of extubation after 10 days of the therapy and radiological imaging suggestive of improvement in the lung fields 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In a 3 months span of its first appearance in Wuhan, China, it was declared as Pandemic by WHO. In India about 3-10% patients are requiring intubation and 10-20% are requiring ICU admission 2,3 . The mortality rate was 49% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Results from a single-center open-label single-arm study in Northern Macedonia [ 90 ] and from a multicenter trial lead in Mexico City comparing CRRT with AN69 vs. oXiris in COVID-19 patients [ 91 ] are eagerly expected. Interestingly, the use of Cytosorb and the oXiris cartridge in critically ill COVID-19 patients improves the oxygenation index, reduces CRP, and warrants hemodynamic stabilization in previous observational studies [ 92 , 93 , 94 , 95 , 96 ].…”
Section: Role Of Dialysis In the Treatment Of Patients With Covid-19 ...mentioning
confidence: 98%
“…The patients showed significant improvement in clinical outcomes and biochemical parameters post-CytoSorb ® therapy. The mean arterial pressure (MAP) improved, C-reactive protein levels decreased post-therapy, and the patients were discharged [120]. Song et al reported the high survival rates of critically-ill COVID-19 patients on extracorporeal membrane oxygenation by using CytoSorb ® therapy in the retrospective multi-centric study [121].…”
Section: Innovative Therapeutic Alternativesmentioning
confidence: 99%
“…Song et al reported the high survival rates of critically-ill COVID-19 patients on extracorporeal membrane oxygenation by using CytoSorb ® therapy in the retrospective multi-centric study [121]. Table 2 summarizes the peer-reviewed articles examining the benefits of CytoSorb ® treatment [115,116,120,[122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137]. Most of the evidence regarding the effectiveness of CytoSorb ® is based on case series, case studies and retrospective reports.…”
Section: Innovative Therapeutic Alternativesmentioning
confidence: 99%